The Effect Of Price, Brand Image, And Social Media Marketing On The Purchase Decision Of Ciptadent Toothpaste Products - Nico Dwi Saputro; Ezra Karamang (International Journal of Marketing & Human Resource Research, 2026)
Examining how factors, including pricing, brand perception, and social media advertising, influence consumers' decisions to buy Ciptadent toothpaste is the primary goal of this research. This research uses both descriptive and verificatory methodologies within a quantitative framework. We used the Slovin formula to calculate our sample size after randomly selecting 100 Ciptadent product buyers to complete our surveys. A variety of statistical tests, including multiple linear regression, t-tests, F-tests, and coefficient-of-determination tests, were used to support the data analysis. Price has a negative, statistically significant influence on consumers' propensity to buy, whereas brand image and social media marketing have positive, statistically significant effects. All three of these factors, price, brand perception, and social media marketing, contribute significantly to consumers' final judgments. The three independent variables account for 98.7 percent of the variance in purchase choices, with additional, non-research-related factors explaining the remaining 1.3 percent (R² = 0.987). In order to increase customer purchase choices, these results highlight the significance of setting competitive pricing that are in accordance with the perceived value of the product, improving social media marketing methods, and boosting brand image.